Monitoring the Intracellular Tacrolimus Concentration in Kidney Transplant Recipients with Stable Graft Function - Han, Seung Seok (PLoS One, 2016)
Although monitoring the intracellular concentration of immunosuppressive agents may be a promising approach to individualizing the therapy after organ transplantation, additional studies on this issue are needed prior to its clinical approval. We investigated the relationship between intracellular and whole blood concentrations of tacrolimus (IC-TAC and WB-TAC, respectively), the factors affecting this relationship, and the risk of rejection based upon IC-TAC in stable kidney recipients. Both IC-TAC and WB-TAC were measured simultaneously in 213 kidney recipients with stable graft function using LC-MS/MS. The tacrolimus ratio was defined as IC-TAC per WB-TAC. The genetic polymorphism of ABCB1 gene and flow cytometric analyses were conducted to probe the correlation between tacrolimus concentrations and the immunoreactivity status as a potential risk of rejection, respectively. The correlation between IC-TAC and WB-TAC was relatively linear (r = 0.67; P<0.001). The factors affecting the tacrolimus ratio were sex, hematocrit, and the transplant duration, as follows: a high tacrolimus ratio was noted in female patients, patients with a low hematocrit, and patients with a short transplant period. However, the tacrolimus ratio did not reflect the prior clinical outcomes (e.g., rejection) or the genetic polymorphism of ABCB1. After stimulation with phorbol-12-myristate 13-acetate and ionomycin, the proportion of T cells producing interferon-gamma or interleukin-2 was higher in the low-IC-TAC group than in the high-IC-TAC group. Further studies are required to evaluate the value of the intracellular tacrolimus concentrations in several clinical settings, such as rejection, infection, and drug toxicity.